Salvage Liver Transplantation for Recurrent Hepatocellular Carcinoma within UCSF Criteria after Liver Resection - Liu, Fei; Wei, Yonggang; Wang, Wentao; Chen, Kefei; Yan, Lvnan; Wen, Tianfu; Zhao, Jichun; Xu, Mingqing; Li, Bo (PLOS ONE, 2012)
Background Salvage liver transplantation (SLT) is restricted to patients who develop hepatocellular carcinoma (HCC) recurrence within Milan criteria (MC). Little is known about outcomes for SLT in patients with recurrent HCC within University of California San Francisco (UCSF) criteria after liver resection (LR). Methods Between January 2001 and December 2011, 380 patients with HCC meeting UCSF criteria, 200 of which were resected (LR group) from a perspective of SLT in case of recurrence, and 180 directly underwent LT (PLT). We compared patient characteristics, perioperative and long-term outcomes between SLT and PLT groups. We also assessed the outcome of LR and PLT groups. Results Among the 200 patients in LR group, 86 (43%) developed HCC recurrence and 15/86 (17%) of these patients presented HCC recurrence outside UCSF criteria. Only 39 of the 86 patients underwent SLT, a transplantation rate of 45% of patients with HCC recurrence. Compared with PLT group, LR group showed lower overall survival rate (P = 0.005) and higher recurrence rate (P = 0.006). Although intraoperative blood loss and required blood transfusion were more frequent in SLT group, the perioperative mortality and posttransplant complications were similar in SLT and PLT groups. The overall survival and recurrence rates did not significantly differ between the two groups. When stratifying by graft type in the SLT group, overall survival and recurrence rates did not significantly differ between deceased donor LT (DDLT) and living donor LT (LDLT) groups. In the subgroup analysis by MC, similar results were observed between patients with recurrent HCC meeting MC and patients with recurrent HCC beyond MC but within UCSF criteria. Conclusion Our single institution experience demonstrated that prior hepatectomy and SLT for recurrent HCC within UCSF criteria was feasible and SLT could achieve the same outcome as PLT.